What do popular YouTubeTM videos say about vaccines?. (19th January 2017) - Basch, C. H.; Zybert, P.; Reeves, R.; Basch, C. E.
Summary: Background: The unregulated social network YouTube TM has become an increasingly popular source of information on health topics such as vaccine safety. With a reach of over one billion users per month, the potential for misinformation is significant. Methods: Using the keywords 'vaccine safety' and 'vaccines and children', 87 of the most widely viewed YouTube TM videos were identified and analyzed for content, author status and view count. Results: The range of view counts was 25 532 to 6 229 835, with a median of 62 075 views per video. Most videos ( n = 74, 85.1%) were devoted exclusively to the topic of vaccination. The three most common sources of these YouTube TM videos were consumers (27.6%), TV‐based or Internet‐based news (26.4%) and individual health professionals (25.3%). Top topics covered were autism causality (47.1% of videos), undisclosed or poorly understood risks (42.5%), adverse reactions (40.2%) and thimerosol or mercury in vaccines (36.8%). The majority of videos (65.5%) discouraged the use of vaccines. Conclusion: Health professionals should be aware of the widely disseminated vaccination information available on the Internet and should appreciate its possible effect on the public.